Preparation method of yttrium-doped lithium-rich manganese-based positive electrode material, positive electrode sheet and lithium ion battery

CN123017850APending Publication Date: 2026-10-30NANKAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611115109.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]针对现有技术中富锂锰基正极材料存在的上述缺陷,本发明的目的之一是提供一种钇掺杂富锂锰基正极材料的制备方法,旨在解决现有富锂锰基正极材料经元素掺杂改性在提升其循环稳定性时,难以兼顾首圈充放电效率、放电比容量的技术难题

Benefits of technology

[0023](1)将钇元素掺杂至具备大层间距的氧化物前驱体中,掺杂过程不会破坏前驱体原有晶体结构,可完整保留材料高放电比容量、高首圈库仑效率;同时掺杂形成强 Y-O 化学键,提升析氧反应能垒,有效抑制晶格氧流失与过渡金属溶出,进而显著缓解材料循环过程中的容量及电压衰减现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017850A_ABST
    Figure CN123017850A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of lithium battery positive electrode material, and relates to a preparation method of yttrium-doped lithium-rich manganese-based positive electrode material, a positive electrode sheet and a lithium ion battery. The precursor is first heat-treated to obtain an oxide precursor with a large interlayer spacing, and then a yttrium-doped lithium-rich manganese-based positive electrode material is prepared by a solid-phase sintering method. The present application can effectively incorporate yttrium ions into the bulk phase of the material without damaging the original crystal structure of the material. On the basis of not damaging the high discharge specific capacity and high initial coulombic efficiency performance of the material, strong Y-O chemical bonds are introduced to effectively improve the oxygen evolution reaction energy barrier, significantly inhibit the loss of lattice oxygen, the dissolution of transition metals and the structural phase transition phenomenon in the cycle process, effectively alleviate the capacity decay and voltage decay problems in the cycle process of the material, and greatly improve the cycle stability performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery cathode material technology, and more specifically, relates to a method for preparing a yttrium-doped lithium-rich manganese-based cathode material, a cathode sheet, and a lithium-ion battery. Background Technology

[0002] Currently, the most widely used cathode materials for lithium-ion batteries in industry mainly include high-nickel ternary cathodes (with a capacity of ~200 mAh g). -1 Lithium iron phosphate cathode (capacity ~160 mAh g) -1 However, their specific capacity is insufficient to meet the high-end demands of improved range for new energy vehicles and efficient operation of large-scale energy storage. In recent years, layered lithium-rich manganese-based cathode materials have become core candidate cathode materials for next-generation high-energy-density lithium batteries due to their excellent reversible electrochemical performance, attracting widespread attention in the industry. Their reversible capacity can reach 250 mAh g⁻¹. -1 The above describes the achievement of this ultra-high specific capacity. It relies not only on the redox reaction of transition metal cations but also on the redox reaction of oxygen anions, specifically including the reversible redox reaction of oxygen anions within the bulk phase and the irreversible oxygen release reaction of oxygen anions on the material surface. The irreversible oxygen release process mainly includes two consecutive steps: the first step is the direct release of oxygen from the material surface; the second step is the gradual diffusion of oxygen anions from beneath the material surface to the surface, thus achieving continuous oxygen release.

[0003] However, when transition metal atoms migrate to adjacent lithium layers, the original layered structure of the layered lithium-rich manganese-based cathode material transforms into a spinel-like structure. This structural transformation significantly reduces the diffusion rate of lithium ions, leading to capacity decay, voltage drop, and electrochemical performance degradation in lithium-ion batteries, failing to meet the large-scale and long-term application requirements of the new energy industry. Furthermore, the aforementioned irreversible oxygen release process induces severe interfacial side reactions, further hindering the industrialization of layered lithium-rich manganese-based cathode materials. In summary, effectively suppressing irreversible oxygen release while maintaining the structural stability of layered lithium-rich manganese-based cathode materials and preserving their oxygen anion redox reactivity is a key technological challenge for achieving the industrial application of high-energy-density layered lithium-rich manganese-based cathode materials and promoting the performance upgrade of lithium-ion batteries.

[0004] Numerous studies have confirmed that bulk doping can suppress the dissolution and oxygen loss of transition metals (TMs). Among these, yttrium doping effectively suppresses oxygen loss and TM dissolution due to the increased energy barrier of the oxygen evolution reaction caused by the strong YO bond energy, thereby effectively suppressing capacity / voltage decay during cycling.

[0005] Chinese invention patent application CN 111082044 A discloses a yttrium-doped lithium-rich manganese-based cathode material, its preparation method, and a lithium-ion battery. The method utilizes a high-temperature solid-state process to prepare the yttrium-doped lithium-rich manganese-based cathode material, effectively suppressing capacity and voltage decay during cycling. However, due to the large radius of yttrium ions, the original composition of the precursor is affected during co-precipitation, and the amount of nickel-cobalt-manganese-yttrium source is difficult to control accurately, thus affecting the final composition and structure of the material. Electrochemical data also show that this method reduces the material's first-cycle discharge specific capacity, first-cycle coulombic efficiency, and rate performance.

[0006] Chinese invention patent application CN 113422033 A discloses a yttrium-doped yttrium oxide-coated modified lithium-rich manganese-based cathode material, its preparation method, and its application. By treating the precursor with a Y-containing solution, yttrium ions are doped into layered lithium-rich manganese, achieving yttrium ion doping in the transition metal layer. A uniform yttrium oxide coating is then applied to the surface, effectively improving the stability of the crystal structure of the layered lithium-rich manganese oxide cathode material during cycling. However, yttrium oxide is an inert coating. Although it can protect the material surface, its slow electronic conductivity cannot suppress the bulk crystal structure transformation and may even negatively impact dynamic performance, resulting in a significant decrease in the first-cycle discharge specific capacity. Summary of the Invention

[0007] In view of the above-mentioned defects of lithium-rich manganese-based cathode materials in the prior art, one of the objectives of this invention is to provide a method for preparing yttrium-doped lithium-rich manganese-based cathode materials, aiming to solve the technical problem that it is difficult to simultaneously improve the first-cycle charge-discharge efficiency and discharge specific capacity when modifying existing lithium-rich manganese-based cathode materials by elemental doping.

[0008] The objective of this invention is achieved through the following technical solutions.

[0009] In a first aspect, the present invention provides a method for preparing a yttrium-doped lithium-rich manganese-based cathode material, comprising the following steps:

[0010] Step 1: Prepare a precursor containing nickel, cobalt, and manganese via a co-precipitation reaction;

[0011] Step 2: Heat-treat the precursor at 400~700℃ for 5~10 h to obtain an oxide precursor with expanded interlayer spacing;

[0012] Step 3: Mix the oxide precursor with a lithium source and a yttrium source and then sinter at high temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material.

[0013] Further, the coprecipitation reaction described in step 1 includes: mixing soluble manganese salt, nickel salt and cobalt salt in a molar ratio of Mn:Ni:Co = 4~7:1~4:0.1~1 to form a mixed salt solution, adding it to the reaction vessel in parallel with the complexing agent and precipitant, and controlling the reaction temperature at 40~80℃ and the pH value at 7.0~11.5.

[0014] Furthermore, the heat treatment in step 2 is performed at a temperature of 500–600°C for 5–8 hours.

[0015] Furthermore, the atmosphere for the heat treatment is at least one of air, oxygen, or argon.

[0016] Further, the lithium source mentioned in step 3 is at least one of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, and lithium acetate.

[0017] Further, the yttrium source in step 3 is at least one of yttrium oxide, yttrium nitrate, yttrium acetate, yttrium sulfate, and yttrium carbonate.

[0018] Furthermore, the molar ratio of the oxide precursor, lithium source, and yttrium source in step 3 is 1:1.2:0.15 to 1.

[0019] Furthermore, the high-temperature sintering temperature in step 3 is 500-950°C, and the atmosphere is at least one of air, oxygen, or argon.

[0020] In a second aspect, this disclosure provides a positive electrode sheet, comprising a modified lithium-rich manganese-based positive electrode material prepared by the preparation method of the yttrium-doped lithium-rich manganese-based positive electrode material described in the first aspect.

[0021] Thirdly, this disclosure provides a lithium-ion battery, including the positive electrode sheet described in the second aspect.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] (1) Doping yttrium into an oxide precursor with a large interlayer spacing does not destroy the original crystal structure of the precursor, thus preserving the material’s high discharge specific capacity and high first-cycle coulombic efficiency. At the same time, doping forms strong YO chemical bonds, which enhances the oxygen evolution reaction barrier, effectively suppresses lattice oxygen loss and transition metal dissolution, thereby significantly alleviating the capacity and voltage decay phenomenon during the material’s cycling process.

[0024] (2) The yttrium-doped lithium-rich manganese-based cathode material provided by this invention can simultaneously obtain multiple modification advantages. When the yttrium-doped lithium-rich manganese-based cathode material is used for electrochemical performance testing of lithium-ion batteries, the experimental results show that the yttrium-doped lithium-rich manganese-based cathode material has a capacity retention rate of 95.92% after 200 cycles at 1C, and the voltage decay is only 0.7495 mV / cycle. It still has 296.54 mAh g at 0.1C. -1 It has a high specific capacity and a first-week coulomb efficiency of 88.03%.

[0025] (3) The preparation process of the yttrium-doped lithium-rich manganese-based cathode material provided by this invention is simple and easy to promote. By adjusting the concentration and type of yttrium source, the heat treatment temperature of the precursor, and the sintering temperature, the amount of yttrium doping can be effectively adjusted, thereby regulating the electrochemical performance of the electrode material. This is an effective method to improve the cycle stability of lithium-rich manganese-based cathode materials. This method is universal and can be extended to other transition metal-doped lithium-rich manganese-based systems, such as tin, magnesium, aluminum, niobium, molybdenum, zirconium, and titanium.

[0026] In summary, compared with co-precipitation for yttrium doping and liquid-phase precursor doping, heat-treated precursors yield oxide precursors with large interlayer spacing, followed by solid-phase doping. This allows the yttrium source to be effectively incorporated into the bulk phase of the material without damaging its structure. This enables the material to maintain its high discharge specific capacity and first-cycle coulombic efficiency while significantly suppressing voltage and capacity decay, thus improving the material's cycle stability. Attached Figure Description

[0027] Figure 1 The image shows a scanning electron microscope (SEM) image of the sample obtained in Comparative Example 1.

[0028] Figure 2 The image shown is a scanning electron microscope (SEM) image of the sample obtained in Example 2.

[0029] Figure 3 This is a focused ion beam electron microscope image of the sample obtained in Example 2;

[0030] Figure 4 The X-ray diffraction patterns of the samples obtained in Examples 1-4 and Comparative Example 1 are shown below.

[0031] Figure 5 The Raman spectra of the samples obtained in Examples 1-4 and Comparative Example 1 are shown.

[0032] Figure 6 X-ray photoelectron spectra of the sample obtained in Example 2 at different etching times for Y 3d;

[0033] Figure 7 The voltage drop of the samples obtained in Example 2 and Comparative Example 1 at a current density of 1 C is shown in the graph.

[0034] Figure 8 The graph shows the cycling performance of the samples obtained in Example 2 and Comparative Example 1 at a current density of 1 C.

[0035] Figure 9 The first charge-discharge curves of the samples obtained in Examples 1-4 and Comparative Example 1 at a current density of 0.1 C are shown.

[0036] Figure 10 The first charge-discharge curves of the samples obtained in Example 2 and Comparative Examples 2-3 at a current density of 0.1 C are shown.

[0037] Figure 11 The first charge-discharge curves of the samples obtained in Example 2 and Comparative Examples 4-5 at a current density of 0.1 C are shown. Detailed Implementation

[0038] Numerous specific details are set forth in the following description to provide a full understanding of the invention. However, the invention can be practiced in many other ways different from those described herein, and similar modifications can be made by those skilled in the art without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0040] Unless otherwise specified, the raw materials or chemical reagents used in the embodiments of this invention are obtained through conventional commercial channels.

[0041] Example 1

[0042] This embodiment provides a method for preparing a yttrium-doped lithium-rich manganese-based cathode material, including the following steps:

[0043] A nickel-cobalt-manganese carbonate precursor was prepared by co-precipitation reaction: Soluble MnCO3·2H2O, CoCO3·H2O, and NiCO3·2H2O were weighed according to the metal element ratio Mn:Co:Ni = 4:1:1. Deionized water was added and stirred at 25℃ and 400 r / min to dissolve the mixture, yielding a 1.0 mol / L mixed metal salt solution. Simultaneously, a 1.5 mol / L carbonate precipitant solution and a 0.3 mol / L ammonia complexing agent solution were prepared for later use. The reactor was preheated to 60℃, and deionized water was added to adjust the pH to 7.5-9.0. The three solutions were simultaneously and uniformly added dropwise at a rate of 10 mL / min, maintaining the temperature at 60℃ and 400 r / min throughout the process. Stirring at r / min and stabilizing pH at 7.5-9.0, reacting for 12 h, then maintaining the temperature at 200 r / min for 6 h of maturation, followed by solid-liquid separation by centrifugation or filtration. The precipitate was washed three times with deionized water until the conductivity of the washing solution was ≤50 μS / cm. The precipitate was then dried in a 100℃ oven for 12 h, cooled to room temperature, and ground to obtain the carbonate precursor (Mn). 4 / 6 Co 1 / 6 Ni 1 / 6 CO3. Then (Mn) 4 / 6Co 1 / 6 Ni 1 / 6 CO3 was heat-treated in an air-filled muffle furnace at 500°C for 5 h to obtain an oxide precursor with a large interlayer spacing.

[0044] The oxide precursor was weighed and mixed evenly with lithium carbonate and yttrium oxide in a molar ratio of 1:0.6:0.15 in an agate mortar. The mixture was then transferred to a corundum boat and calcined in a muffle furnace under an air atmosphere. The calcination conditions were as follows: first, pre-calcination at 500℃ for 6 h, then calcination at 850℃ for 12 h, with a heating rate of 3℃ / min. Finally, the mixture was naturally cooled to room temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material, named 0.3%Y-LRMO.

[0045] Example 2

[0046] This embodiment provides a method for preparing a yttrium-doped lithium-rich manganese-based cathode material, including the following steps:

[0047] A nickel-cobalt-manganese carbonate precursor was prepared by co-precipitation reaction: Soluble MnCO3·2H2O, CoCO3·H2O, and NiCO3·2H2O were weighed according to the metal element ratio Mn:Co:Ni = 4:1:1. Deionized water was added and stirred at 25℃ and 400 r / min to dissolve the mixture, yielding a 1.0 mol / L mixed metal salt solution. Simultaneously, a 1.5 mol / L carbonate precipitant solution and a 0.3 mol / L ammonia complexing agent were prepared for later use. The reactor was preheated to 60℃, and deionized water was added to adjust the pH to 7.5-9.0. The three solutions were simultaneously and uniformly added dropwise (dropping rate 10 mL / min), maintaining a constant temperature of 60℃, 400 r / min stirring, and pH stable at 7.5-9.0 throughout the reaction. After 12 h of reaction, the mixture was aged at the same temperature and 200 r / min stirring for 6 hours. h, then solid-liquid separation was performed by centrifugation or vacuum filtration. The precipitate was washed three times with deionized water until the conductivity of the washing solution was ≤50μS / cm. The precipitate was then placed in a 100℃ oven for constant temperature drying for 12 h. After cooling to room temperature and grinding, the carbonate precursor (Mn) was obtained. 4 / 6 Co 1 / 6 Ni 1 / 6 CO3. Then (Mn) 4 / 6 Co 1 / 6 Ni 1 / 6 CO3 was heat-treated in an air-filled muffle furnace at 500°C for 5 h to obtain an oxide precursor with a large interlayer spacing.

[0048] The oxide precursor was weighed and mixed evenly with lithium carbonate and yttrium oxide in a molar ratio of 1:0.6:0.25 in an agate mortar. The mixture was then transferred to a corundum boat and calcined in a muffle furnace under an air atmosphere. The calcination conditions were as follows: first, pre-calcination at 500℃ for 6 h, then calcination at 850℃ for 12 h, with a heating rate of 3℃ / min. Finally, the mixture was naturally cooled to room temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material, named 0.5%Y-LRMO.

[0049] Example 3

[0050] This embodiment provides a method for preparing a yttrium-doped lithium-rich manganese-based cathode material, including the following steps:

[0051] A nickel-cobalt-manganese carbonate precursor was prepared by co-precipitation reaction: Soluble MnCO3·2H2O, CoCO3·H2O, and NiCO3·2H2O were weighed according to the metal element ratio Mn:Co:Ni = 4:1:1. Deionized water was added and stirred at 25℃ and 400 r / min to dissolve the mixture, yielding a 1.0 mol / L mixed metal salt solution. Simultaneously, a 1.5 mol / L carbonate precipitant solution and a 0.3 mol / L ammonia complexing agent were prepared for later use. The reactor was preheated to 60℃, and deionized water was added to adjust the pH to 7.5-9.0. The three solutions were simultaneously and uniformly added dropwise (dropping rate 10 mL / min), maintaining a constant temperature of 60℃, 400 r / min stirring, and pH stable at 7.5-9.0 throughout the reaction. After 12 h of reaction, the mixture was aged at the same temperature and 200 r / min stirring for 6 hours. h, then solid-liquid separation was performed by centrifugation or vacuum filtration. The precipitate was washed three times with deionized water until the conductivity of the washing solution was ≤50μS / cm. The precipitate was then placed in a 100℃ oven for constant temperature drying for 12 h. After cooling to room temperature and grinding, the carbonate precursor (Mn) was obtained. 4 / 6 Co 1 / 6 Ni 1 / 6 CO3. Then (Mn) 4 / 6 Co 1 / 6 Ni 1 / 6 CO3 was heat-treated in an air-filled muffle furnace at 500°C for 5 h to obtain an oxide precursor with a large interlayer spacing.

[0052] The oxide precursor was weighed and mixed evenly with lithium carbonate and yttrium oxide in a molar ratio of 1:0.6:0.5 in an agate mortar. The mixture was then transferred to a corundum boat and calcined in a muffle furnace under an air atmosphere. The calcination conditions were as follows: first, pre-calcination at 500℃ for 6 h, then calcination at 850℃ for 12 h, with a heating rate of 3℃ / min. Finally, the mixture was naturally cooled to room temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material, named 1.0%Y-LRMO.

[0053] Example 4

[0054] This embodiment provides a method for preparing a yttrium-doped lithium-rich manganese-based cathode material, including the following steps:

[0055] A nickel-cobalt-manganese carbonate precursor was prepared by co-precipitation reaction: Soluble MnCO3·2H2O, CoCO3·H2O, and NiCO3·2H2O were weighed according to the metal element ratio Mn:Co:Ni = 4:1:1. Deionized water was added and stirred at 25℃ and 400 r / min to dissolve the mixture, yielding a 1.0 mol / L mixed metal salt solution. Simultaneously, a 1.5 mol / L carbonate precipitant solution and a 0.3 mol / L ammonia complexing agent were prepared for later use. The reactor was preheated to 60℃, and deionized water was added to adjust the pH to 7.5-9.0. The three solutions were simultaneously and uniformly added dropwise (dropping rate 10 mL / min), maintaining a constant temperature of 60℃, 400 r / min stirring, and pH stable at 7.5-9.0 throughout the reaction. After 12 h of reaction, the mixture was aged at the same temperature and 200 r / min stirring for 6 hours. h, then solid-liquid separation was performed by centrifugation or vacuum filtration. The precipitate was washed three times with deionized water until the conductivity of the washing solution was ≤50μS / cm. The precipitate was then placed in a 100℃ oven for constant temperature drying for 12 h. After cooling to room temperature and grinding, the carbonate precursor (Mn) was obtained. 4 / 6 Co 1 / 6 Ni 1 / 6 CO3. Then (Mn) 4 / 6 Co 1 / 6 Ni 1 / 6 CO3 was heat-treated in an air-filled muffle furnace at 500°C for 5 h to obtain an oxide precursor with a large interlayer spacing.

[0056] The oxide precursor was weighed and mixed evenly with lithium carbonate and yttrium oxide in a molar ratio of 1:0.6:1 in an agate mortar. The mixture was then transferred to a corundum boat and calcined in a muffle furnace under an air atmosphere. The calcination conditions were as follows: first, pre-calcination at 500℃ for 6 hours, then calcination at 850℃ for 12 hours, with a heating rate of 3℃ / min. Finally, the mixture was naturally cooled to room temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material, named 2.0%Y-LRMO.

[0057] Comparative Example 1

[0058] This embodiment provides a method for preparing a lithium-rich manganese-based cathode material without yttrium doping, including the following steps:

[0059] A nickel-cobalt-manganese carbonate precursor was prepared by co-precipitation reaction: Soluble MnCO3·2H2O, CoCO3·H2O, and NiCO3·2H2O were weighed according to the metal element ratio Mn:Co:Ni = 4:1:1. Deionized water was added and stirred at 25℃ and 400 r / min to dissolve the mixture, yielding a 1.0 mol / L mixed metal salt solution. Simultaneously, a 1.5 mol / L carbonate precipitant solution and a 0.3 mol / L ammonia complexing agent were prepared for later use. The reactor was preheated to 60℃, and deionized water was added to adjust the pH to 7.5-9.0. The three solutions were simultaneously and uniformly added dropwise (dropping rate 10 mL / min), maintaining a constant temperature of 60℃, 400 r / min stirring, and pH stable at 7.5-9.0 throughout the reaction. After 12 h of reaction, the mixture was aged at the same temperature and 200 r / min stirring for 6 hours. h, then solid-liquid separation was performed by centrifugation or vacuum filtration. The precipitate was washed three times with deionized water until the conductivity of the washing solution was ≤50μS / cm. The precipitate was then placed in a 100℃ oven for constant temperature drying for 12 h. After cooling to room temperature and grinding, the carbonate precursor (Mn) was obtained. 4 / 6 Co 1 / 6 Ni 1 / 6 CO3. Then (Mn) 4 / 6 Co 1 / 6 Ni 1 / 6 CO3 was heat-treated in an air-filled muffle furnace at 500°C for 5 h to obtain an oxide precursor with a large interlayer spacing.

[0060] The oxide precursor and lithium carbonate were weighed and mixed evenly in an agate mortar at a molar ratio of 1:0.6. The mixture was then transferred to a corundum boat and calcined in a muffle furnace under air atmosphere. The calcination conditions were: first, pre-calcination at 500℃ for 6 h; then, calcination at 850℃ for 12 h; with a heating rate of 3℃ / min; and finally, natural cooling to room temperature to obtain the original lithium-rich manganese-based cathode material with the molecular formula Li. 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2, named LRMO.

[0061] Comparative Example 2

[0062] The difference from Example 2 is that (Mn) is omitted. 4 / 6 Co 1 / 6 Ni 1 / 6 The step of heat-treating CO3 in an air-atmospheric furnace at 500°C for 5 h to obtain an oxide precursor with a large interlayer spacing is to directly apply (Mn) 4 / 6 Co 1 / 6 Ni 1 / 6CO3, lithium carbonate, and yttrium oxide were weighed in an agate mortar at a molar ratio of 1:0.6:0.25 and mixed evenly. The mixture was then transferred to a corundum boat and calcined in a muffle furnace under an air atmosphere. The calcination conditions were: first, pre-calcination at 500℃ for 6 h, then calcination at 850℃ for 12 h, with a heating rate of 3℃ / min. Finally, the mixture was naturally cooled to room temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material, named 0.5% Y-LRMO by direct solid-state method.

[0063] Comparative Example 3

[0064] Step 1: Preparation of precursors and raw materials

[0065] The carbonate precursor (Mn) was prepared using the exact same method as in Example 2. 4 / 6 Co 1 / 6 Ni 1 / 6 CO3. The lithium source is lithium carbonate, and the yttrium source is changed to yttrium nitrate hexahydrate, which is soluble in ethanol, to facilitate impregnation.

[0066] Step 2: Liquid phase impregnation (for unburned carbonate precursors)

[0067] Weigh 10g of carbonate precursor (without any heat treatment). Calculate the required mass of yttrium nitrate so that the molar ratio of Y:(Ni+Co+Mn) in the final product is the same as in Example 2 (0.5%). Dissolve yttrium nitrate in 50mL of anhydrous ethanol, add the precursor powder, and stir magnetically at room temperature for 6 hours.

[0068] Step 3: Evaporate the solvent and mix with the lithium source.

[0069] The above suspension was stirred and the ethanol was evaporated in an 80°C water bath to obtain a precursor powder adsorbed with yttrium ions. This powder was weighed with lithium carbonate at a molar ratio of Li:TM = 1.2:1 (the total amount of TM remained unchanged), and then manually ground and mixed in an agate mortar for 40 minutes.

[0070] Step 4: High-temperature sintering

[0071] The above mixed powder was transferred to a corundum ark and calcined in a muffle furnace under air atmosphere. The calcination conditions were: first, pre-calcination at 500℃ for 6 h, then calcination at 850℃ for 12 h, with a heating rate of 3℃ / min, and finally natural cooling to room temperature to obtain yttrium-doped lithium-rich manganese-based cathode material, named 0.5% Y-LRMO by liquid phase impregnation.

[0072] Comparative Example 4

[0073] The difference from Example 2 is that (Mn) is then added. 4 / 6 Co 1 / 6 Ni 1 / 6CO3 was heat-treated in an air-atmospheric furnace at 200°C for 5 hours. The effect of the heat treatment temperature was compared, including the following steps:

[0074] A nickel-cobalt-manganese carbonate precursor was prepared by co-precipitation reaction: Soluble MnCO3·2H2O, CoCO3·H2O, and NiCO3·2H2O were weighed according to the metal element ratio Mn:Co:Ni = 4:1:1. Deionized water was added and stirred at 25℃ and 400 r / min to dissolve the mixture, yielding a 1.0 mol / L mixed metal salt solution. Simultaneously, a 1.5 mol / L carbonate precipitant solution and a 0.3 mol / L ammonia complexing agent solution were prepared for later use. The reactor was preheated to 60℃, and deionized water was added to adjust the pH to 7.5-9.0. The three solutions were simultaneously and uniformly added dropwise at a rate of 10 mL / min, maintaining the temperature at 60℃ and 400 r / min throughout the process. Stirring at r / min and stabilizing pH at 7.5-9.0, reacting for 12 h, then maintaining the temperature at 200 r / min for 6 h of maturation, followed by solid-liquid separation by centrifugation or filtration. The precipitate was washed three times with deionized water until the conductivity of the washing solution was ≤50 μS / cm. The precipitate was then dried in a 100℃ oven for 12 h, cooled to room temperature, and ground to obtain the carbonate precursor (Mn). 4 / 6 Co 1 / 6 Ni 1 / 6 CO3. Then (Mn) 4 / 6Co 1 / 6 Ni 1 / 6 CO3 was heat-treated in an air-filled muffle furnace at 200°C for 5 h to obtain an oxide precursor with a large interlayer spacing.

[0075] The oxide precursor was weighed and mixed evenly with lithium carbonate and yttrium oxide in a molar ratio of 1:0.6:0.25 in an agate mortar. The mixture was then transferred to a corundum boat and calcined in a muffle furnace under an air atmosphere. The calcination conditions were as follows: first, pre-calcination at 500℃ for 6 h, then calcination at 850℃ for 12 h, with a heating rate of 3℃ / min. Finally, the mixture was naturally cooled to room temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material, named low-temperature heat-treated 0.5% Y-LRMO.

[0076] Comparative Example 5

[0077] The difference from Example 2 is that (Mn) is then added. 4 / 6 Co 1 / 6 Ni 1 / 6 CO3 was heat-treated in an air-filled muffle furnace at 800°C for 5 hours. The effect of the heat treatment temperature was compared, including the following steps:

[0078] A nickel-cobalt-manganese carbonate precursor was prepared by co-precipitation reaction: Soluble MnCO3·2H2O, CoCO3·H2O, and NiCO3·2H2O were weighed according to the metal element ratio Mn:Co:Ni = 4:1:1. Deionized water was added and stirred at 25℃ and 400 r / min to dissolve the mixture, yielding a 1.0 mol / L mixed metal salt solution. Simultaneously, a 1.5 mol / L carbonate precipitant solution and a 0.3 mol / L ammonia complexing agent solution were prepared for later use. The reactor was preheated to 60℃, and deionized water was added to adjust the pH to 7.5-9.0. The three solutions were simultaneously and uniformly added dropwise at a rate of 10 mL / min, maintaining the temperature at 60℃ and 400 r / min throughout the process. Stirring at r / min and stabilizing pH at 7.5-9.0, reacting for 12 h, then maintaining the temperature at 200 r / min for 6 h of maturation, followed by solid-liquid separation by centrifugation or filtration. The precipitate was washed three times with deionized water until the conductivity of the washing solution was ≤50 μS / cm. The precipitate was then dried in a 100℃ oven for 12 h, cooled to room temperature, and ground to obtain the carbonate precursor (Mn). 4 / 6 Co 1 / 6 Ni 1 / 6 CO3. Then (Mn) 4 / 6Co 1 / 6 Ni 1 / 6 CO3 was heat-treated in an air-filled muffle furnace at 800°C for 5 h to obtain an oxide precursor with a large interlayer spacing.

[0079] The oxide precursor was weighed and mixed evenly with lithium carbonate and yttrium oxide in a molar ratio of 1:0.6:0.25 in an agate mortar. The mixture was then transferred to a corundum boat and calcined in a muffle furnace under an air atmosphere. The calcination conditions were as follows: first, pre-calcination at 500℃ for 6 h, then calcination at 850℃ for 12 h, with a heating rate of 3℃ / min. Finally, the mixture was naturally cooled to room temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material, named 0.5% Y-LRMO.

[0080] The samples prepared in Examples 1-4 and Comparative Examples 1-5 were characterized for their performance, and the results are as follows: Figures 1-6 As shown.

[0081] Figure 2 This is a scanning electron microscope (SEM) image of the yttrium-doped lithium-rich manganese-based cathode material provided in Example 2. Figure 1 This is a scanning electron microscope (SEM) image of the undoped yttrium-rich lithium-manganese-based cathode material provided in Comparative Example 1. Figures 1-2 It can be seen that the particle diameters of the materials obtained in Example 2 and Comparative Example 1 are both in the range of 10-15 µm, which indicates that the yttrium-doped lithium-rich manganese-based cathode material provided in Example 2 maintains a good morphology without any damage.

[0082] Figure 3The image shown is a focused ion beam electron microscope image of the sample obtained in Example 2. The spherical particles of the material obtained in Example 2 were cut and subjected to energy dispersive spectroscopy analysis. It was observed that yttrium was uniformly distributed inside the material, indicating that the method successfully doped yttrium into the bulk structure of the material and had excellent doping uniformity.

[0083] Figure 4 The X-ray diffraction patterns of the samples obtained in Examples 1-4 and Comparative Example 1 are shown below. Figure 4 The x-axis represents twice the angle, in degrees, and the y-axis represents intensity. Figure 4 It can be seen that the yttrium-doped materials 0.3% Y-LRMO, 0.5% Y-LRMO, 1.0% Y-LRMO, and 2.0% Y-LRMO have essentially the same crystal structure as LRMO, corresponding to the α-NaFeO2 structure in space group R-3m and the monoclinic Li2MnO3 structure in space group C2 / m. No impurity phases appear, indicating that heat treatment of the precursor before doping does not cause damage to the intrinsic structure of the material. Moreover, compared with Comparative Example 1, the diffraction peaks of the materials in Examples 1-4 are all shifted to lower angles, which also indicates that the interlayer spacing of the material increases after doping.

[0084] Figure 5 The Raman spectra of the samples obtained in Examples 1-4 and Comparative Example 1 are shown. Figure 5 The x-axis represents the wave number, in cm. -1 The vertical axis represents intensity, from Figure 5 It can be seen that 485 and 595 cm -1 The two main peaks at point E correspond to the R-3m layered structure, respectively. g and A 1g Pattern, 350-450 cm -1 The range corresponds to the Li₂MnO₃ phase. Compared with the original LRMO provided in Comparative Example 1, the yttrium-doped materials A provided in Examples 1-4... 1g The blue shift in the peak may be due to the presence of Y doping in the lithium layer, causing local lattice contraction in the transition metal layer and shortening the Mn-O bond length. This further indicates that yttrium doping has entered the bulk phase of the material and occupies lithium sites.

[0085] Figure 6 The X-ray photoelectron spectra of Y 3d under different etching times for 0.5% Y-LRMO provided in Example 2 show that the characteristic peak of Y 3d is always present as the etching depth increases, which indicates that Y element is uniformly incorporated into the crystal lattice.

[0086] The samples obtained from Comparative Examples 1-5 and Examples 1-4 were used as positive electrode materials for lithium-ion batteries to prepare positive electrode sheets. Specifically, the prepared positive electrode material powder was mixed with acetylene black (conductive agent) and polyvinylidene fluoride (PVDF, binder) at a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added as a dispersant. The mixture was then ground into a slurry. Subsequently, the slurry was uniformly coated onto aluminum foil, vacuum dried at 100°C for 12 h, and then transferred to an argon atmosphere glove box for later use.

[0087] Half-cells were assembled in an argon-atmospheric glove box. Using lithium metal as the counter electrode and 1 M LiPF6, ethylene carbonate (EC) / diethyl carbonate (DEC) (by volume, EC:DEC = 1:1) as the electrolyte, CR2032 coin cells were assembled and charged / discharged using a constant current charge / discharge mode. Figure 7 , Figure 8 The voltage drop and cycling performance of the cathode material samples obtained in Example 2 and Comparative Example 1 at a current density of 1 C (1 C = 250 mA / g) are shown respectively. After 200 cycles, the voltage decay of 0.5% Y-LRMO is only 0.7495 mV / cycle, with a capacity retention of up to 95.92%, while the voltage decay of LRMO is 1.761 mV / cycle, with a capacity retention of only 78.65%. Figure 9 The first-cycle charge-discharge curves of the cathode material samples obtained in Examples 1-4 and Comparative Example 1 at a current density of 0.1 C are shown. The first-cycle discharge specific capacity and the first-cycle coulombic efficiency are 270.14 mAh g⁻¹. -1 , 82.62% (LRMO); 278.07 mAh g -1 , 82.96% (0.3%Y-LRMO); 296.54 mAh g -1 , 88.03% (0.5%Y-LRMO); 289.76 mAhg -1 , 87.44% (1.0%Y-LRMO); 269.25 mAh g -1 80.72% (2.0% Y-LRMO). This indicates that the material synthesized by this method maintains its high discharge specific capacity and first-cycle coulombic efficiency while significantly suppressing voltage and capacity decay, thus improving the material's cycle stability.

[0088] Figure 10 The first charge-discharge curves of the cathode material samples obtained in Example 2 and Comparative Examples 2-3 are shown at a current density of 0.1 C. The first-cycle discharge specific capacity of the 0.5% Y-LRMO obtained in Example 2 is 296.54 mAh g⁻¹. -1 Compared to the first-cycle coulombic efficiency of 88.03%, the first-cycle discharge specific capacity of the direct solid-state method 0.5% Y-LRMO obtained in Comparative Example 2 was only 236.58 mAh g⁻¹.-1 The first-cycle coulombic efficiency is only 67.96%. This performance is significantly worse than that of Example 2 of this invention, indicating that direct solid-phase doping without precursor pre-firing cannot form a large-interlayer-spacing oxide precursor, resulting in Y... 3+ It is difficult to effectively incorporate into the bulk phase, the material has poor layered structure regularity, and high capacity and high first-efficiency cannot be achieved.

[0089] The first-cycle discharge specific capacity of 0.5% Y-LRMO obtained by liquid-phase impregnation method in Comparative Example 3 was only 233.23 mAh g. -1 The first-cycle coulombic efficiency was only 75.07%, which is significantly worse than that of Example 2 of the present invention. This indicates that even through liquid phase impregnation, the Y element is mainly adsorbed on the surface of the precursor and is difficult to be uniformly and deeply incorporated into the bulk phase. Furthermore, the carbonate precursor is not pre-calcined and does not have a large interlayer spacing structure, which leads to uneven subsequent lithiation reaction. Ultimately, the material cannot achieve both high capacity and high cycle stability.

[0090] Figure 11 The first charge-discharge curves of the cathode material samples obtained in Example 2 and Comparative Examples 4-5 at a current density of 0.1 C are shown. The first-cycle discharge specific capacity of the 0.5% Y-LRMO obtained in Example 2 is 296.54 mAh g⁻¹. -1 Compared to the initial coulombic efficiency of 88.03%, the initial discharge specific capacity of 0.5% Y-LRMO obtained by low-temperature heat treatment (200℃ precursor sintering) in Comparative Example 4 was only 267.15 mAh g⁻¹. -1 The first-cycle coulombic efficiency was only 77.29%, while the first-cycle discharge specific capacity of 0.5% Y-LRMO obtained by high-temperature heat treatment of the precursor at 800℃ in Comparative Example 5 was only 268.05 mAh g. -1 The first-cycle coulombic efficiency is only 79.04%. The above performance is significantly worse than that of Example 2 of the present invention, indicating that the temperature range for heat treatment of the precursor in this preparation method to obtain oxide precursors with large interlayer spacing is 400-700℃.

[0091] The above embodiments and test results demonstrate that the present invention can effectively incorporate yttrium ions into the bulk phase of the material without damaging the original crystal structure. While maintaining the material's high discharge specific capacity and high first-cycle coulombic efficiency, it introduces strong YO chemical bonds, effectively increasing the oxygen evolution reaction barrier. This significantly suppresses lattice oxygen loss, transition metal dissolution, and structural phase transitions during cycling, effectively alleviating capacity and voltage decay issues during material cycling and greatly improving the material's cycling stability.

[0092] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0093] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for preparing a yttrium-doped lithium-rich manganese-based cathode material, characterized in that, Includes the following steps: Step 1: Prepare a precursor containing nickel, cobalt, and manganese via a co-precipitation reaction; Step 2: Heat-treat the precursor at 400~700℃ for 5~10 h to obtain an oxide precursor with expanded interlayer spacing; Step 3: Mix the oxide precursor with a lithium source and a yttrium source and then sinter at high temperature to obtain a yttrium-doped lithium-rich manganese-based cathode material.

2. The method for preparing yttrium-doped lithium-rich manganese-based cathode material according to claim 1, characterized in that, The coprecipitation reaction described in step 1 includes: mixing soluble manganese salt, nickel salt and cobalt salt in a molar ratio of Mn:Ni:Co = 4~7:1~4:0.1~1 to form a mixed salt solution, adding it to the reaction vessel in parallel with the complexing agent and precipitant, and controlling the reaction temperature at 40~80℃ and the pH value at 7.0~11.

5.

3. The method for preparing the yttrium-doped lithium-rich manganese-based cathode material according to claim 1, characterized in that, The heat treatment in step 2 is performed at a temperature of 500–600°C for 5–8 hours.

4. The method for preparing the yttrium-doped lithium-rich manganese-based cathode material according to claim 1 or 3, characterized in that, The atmosphere for the heat treatment is at least one of air, oxygen, or argon.

5. The method for preparing the yttrium-doped lithium-rich manganese-based cathode material according to claim 1, characterized in that, The lithium source mentioned in step 3 is at least one of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate, and lithium acetate.

6. The method for preparing the yttrium-doped lithium-rich manganese-based cathode material according to claim 1, characterized in that, The yttrium source in step 3 is at least one of yttrium oxide, yttrium nitrate, yttrium acetate, yttrium sulfate, and yttrium carbonate.

7. The method for preparing the yttrium-doped lithium-rich manganese-based cathode material according to claim 1, characterized in that, The molar ratio of the oxide precursor, lithium source and yttrium source in step 3 is 1:1.2:0.15~1.

8. The method for preparing yttrium-doped lithium-rich manganese-based cathode material according to claim 1, characterized in that, The high-temperature sintering temperature in step 3 is 500-950℃, and the atmosphere is at least one of air, oxygen or argon.

9. A positive electrode sheet, characterized in that, This includes yttrium-doped lithium-rich manganese-based cathode materials prepared by the preparation method described in any one of claims 1 to 8.

10. A lithium-ion battery, characterized in that, Includes the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Yttrium-doped lithium-rich manganese-based lithium ion battery positive electrode material, preparation method thereof and lithium ion battery

    CN111082044A

  • Yttrium ion doped yttrium oxide coated and modified lithium-rich manganese-based positive electrode material, as well as preparation method and application

    CN113422033A